The 'mirror test' for estimating visual acuity in infants. Issue 7 (30th November 2009) - Bowman, Richard; McCulloch, Daphne L; Law, Elizabeth; Mostyn, Karen; Dutton, Gordon N
Abstract : Objective: The authors aimed to investigate the association between the distance at which infants fixate their own reflections and visual acuity card testing, and to determine whether this could form the basis of a new clinical test of visual function in infants. Methods: 78 healthy infants under 9 months of age (range 1–266 days, mean 56.5±64SD) were recruited and held close to a mirror such that they attended their own reflections. The distance from the mirror was increased until they no longer held fixation. Binocular acuities were tested with the Teller acuity card procedure. Results: Reliability was rated 'good' in 58 and 60 infants respectively, for mirror distances and for the acuity cards. Data were also included for moderate reliability (n=20 and 14 respectively). The mean mirror distance was 54.9 cm (range 13.5–178, SD=42.8). The mean Teller acuity was 2.19 cycles per degree (range 0.2–14.5, SD=2.8). (Snellen equivalent 6/82, range 6/900–6/12). Mirror distance showed linear correlation with both Teller acuity (R 2 =0.69, p<0.0005) and with age (R 2 =0.73, p<0.0005) by univariate analysis. Using multivariate analysis, only age retained significance. Using logarithmic scales and a logistic growth function for age, correlations were stronger (log mirror distance vs log Teller acuity, R 2 =0.86, p<0.0005; logistic regression of log mirror distance vs log age, R 2 =0.88, p<0.0005), and both retained independent significance in a multivariate model. Conclusion: Mirror fixation distance increases with age in infants and has a good correlation with acuity card results. The portability and ease of use would make it a useful additional tool for detecting impaired visual function in infants.